SNAP-Tag Technology: A General Introduction - Kolberg, Katharina; Puettmann, Christiane; Pardo, Alessa; Fitting, Jenny; Barth, Stefan (Current Pharmaceutical Design, 2013)
Over the past few years, the SNAP-tag technology has become a methodology with great potential in a variety of applications, e.g. the (specific) visualization of individual proteins and studies of protein interaction in living cells. Furthermore, the tag can be used for immunopurification and detection of recombinant proteins or site-specific coupling of recombinant proteins to surfaces. Next to the in vitro applications, it also enables detection of tagged proteins in vivo. This review gives an overview of the SNAP-tag technology in different fields of research and its potential for future developments.
Keywords: site-specific labeling